Larvae of Armases rubripes (Decapoda, Brachyura) in Amazon oligohaline creeks: larval exportation? - Yan Rafael Gillet Santa Brigida; Francielly Alcântara de Lima-Pismel; Ana Beatriz Gama Brito; Jussara Moretto Martinelli-Lemos (Nauplius, 2025)
Abstract Three oligohaline creeks in the Amazon region with different levels of anthropogenic contamination were monitored quarterly regarding the larval density of Armases rubripes and their relationship with temperature, pH, conductivity, salinity, as well as the concentrations of dissolved oxygen, biochemical, oxygen demand, chemical oxygen demand, fecal coliforms, and some dissolved ions, between March 2011 and January 2012. A total of 17,949 A. rubripes larvae in the zoea I developmental stage were identified in the creeks, suggesting export to the continental shelf. Larvae were present every four months, but the highest density occurred in the Amazon rainy season (January), indicating the reproductive peak of the species. Furthermore, we found that the greatest larval abundance and distribution occurred in the most preserved creek, with the lowest concentration of nitrogenous compounds and coliforms. The generalized linear model indicated that conductivity and total suspended solids content are positively correlated with larval density whereas salinity and Ca concentration are negatively correlated with larval density. Therefore, the water quality is concluded to be a structuring factor for the larval population of A. rubripes.